THE INFLUENCE OF CLAIM SERVICE QUALITY ON CUSTOMER LOYALTY: A STUDY ON GENERAL INSURANCE IN INDONESIA - Hayatun Maghfirah (GREET, 2025)
This study examines the relationship between trading volume and stock price volatility in the Indonesian capital market, an emerging market characterized by rapid retail investor participation and sensitivity to global shocks. Using daily data from 100 firms listed on the Indonesia Stock Exchange (IDX), including LQ45 constituents, over the period 2018–2023, the analysis employs panel regression and correlation models with firm size, sector, interest rates, and inflation as control variables. Stock price volatility is measured by the standard deviation of daily returns, while trading volume is captured through absolute and average daily activity. The results reveal a strong positive association between trading activity and price volatility, with a correlation coefficient of 0.65 (p < 0.01). Regression findings indicate that a 1% increase in trading volume corresponds to a 0.5% rise in volatility, confirming that heightened trading intensifies price fluctuations. Sectoral heterogeneity is also evident: technology stocks exhibit the highest sensitivity (r = 0.72), whereas consumer goods show relatively moderate responses. The study contributes to the literature by providing the first large-scale, sector-based empirical evidence from Indonesia, underscoring the importance of trading volume as a volatility driver. Practical implications are offered for investors, regulators, and policymakers in managing risk and fostering market stability.